Cognitive, behavioral and psychiatric symptoms in patients with spinal cord injury: a scoping review - Calderone, Andrea; Cardile, Davide; De Luca, Rosaria; Quartarone, Angelo; Corallo, Francesco; Calabrò, Rocco Salvatore (Frontiers in Psychiatry, 2024)
Spinal Cord Injury (SCI) develops when the spinal cord is damaged and leads to partial or complete loss of motor and/or sensory function, usually below the level of injury. Patients with SCI often experience increased psychiatric symptoms following the injury, and up to 50% of this clinical population appears to have cognitive impairment including decreased processing speed and attention, and difficulties in episodic memory and executive function. Among the behavioral and psychiatric symptoms, depression, anxiety, substance use disorder, and posttraumatic stress disorder are the most common. This review aims to investigate the cognitive, behavioral, or psychiatric symptoms of the patient with SCI and their influence on the rehabilitation process. Studies were identified from an online search of PubMed, Web of Science, Cochrane Library, and Embase databases. Studies published between 2013-2023 were selected. This review has been registered on OSF (n) 3KB2U. We have found that patients with SCI are at high risk of cognitive impairment and experience a wide range of difficulties, including tasks based on processing speed and executive function. This clinical population may experience adjustment disorders with depression and anxiety, as well as other psychiatric symptoms such as fatigue, pain, stress, and suicidal ideation. This review has demonstrated that SCI patients may experience psychiatric symptoms and cognitive impairments that affect their functioning. At the same time, these patients may be more prone to various adjustment and mood disorders. Moreover, these two aspects may interact with each other, causing a range of symptoms, increasing the risk of hospitalization, and delaying the rehabilitation process.